New Insights into the Magnetic Properties of CoFe2O4@SiO2@Au Magnetoplasmonic Nanoparticles - Rareș Bortnic; Adam Szatmari; Gabriela Souca; Răzvan Hirian; Roxana Dudric; Lucian Barbu-Tudoran; Valentin Toma; Rareș Știufiuc; Romulus Tetean; Emil Burzo (Nanomaterials, 2022)
We report the successful synthesis and a complete magnetic characterization of CoFe2O4@SiO2@Au magnetoplasmonic nanoparticles. The CoFe2O4 magnetic nanoparticles were prepared using the hydrothermal method. A subsequent SiO2 shell followed by a plasmonic Au shell were deposited on the magnetic core creating magnetoplasmonic nanoparticles with a core–shell architecture. A spin-glass-type magnetism was shown at the surface of the CoFe2O4 nanograins. Depending on the external magnetic field, two types of spin-glass were identified and analyzed in correlation with the exchange field acting on octahedral and tetrahedral iron sites. The magnetization per formula unit of the CoFe2O4 core is not changed in the case of CoFe2O4@SiO2@Au nanocomposites. The gold nanoparticles creating the plasmonic shell show a giant diamagnetic susceptibility, dependent on their crystallite sizes.